A supramolecular proposal of lignin structure and its relation with the wood properties - Heber S. Abreu; João V.F. Latorraca; Regina P.W. Pereira; Maria Beatriz O. Monteiro; Fábio A. Abreu; Kelysson F. Amparado (Anais da Academia Brasileira de Ciências, 2009)
In spite of the great importance of cellulose the lignin is considered the second most abundant substance of the wood. However, little attention has been given it, mainly to wood properties. The lignin as well as other structural compounds (cellulose and hemicelluloses), has obviously an important role on the wood properties, probably due its composition and existent bonds. In general lignins have β-O-4 (Alkyl Aril Ether) as majoritary bond. This bond in a continued structure form big molecules with spiral conformation as virtual model. Based on this idea, lignins that have high/low β-O-4 content may have differentiated spiraled structures,suggesting different behaviors on the wood properties,which shows that the lignins (Guaicyl:Syringyl (GS)) of angiosperms, for example, which have higher β-O-4 content would present higher spiral conformation than gymnosperms lignins(HG). On the other hand HG lignins have chance of being more anchored on the matrix compound than GS lignins. In this context, the β-O-4 bonds of lignins possibly affect the wood properties, therefore, it is considered relevant for wood technology science discussion. Apesar da grande importância da celulose a lignina é considerada a segunda substância mais abundante da madeira. Entretanto, pouca atenção tem sido dada a ela, principalmente com relação às propriedades da madeira. A lignina assim como outras substâncias (celulose e hemicelulose), tem obviamente um papel importante sobre as propriedades da madeira, provavelmente devido a sua composição e a existências de ligações. Geralmente as ligninas possuem majoritariamente ligaçõesβ-O-4 (Éter Alquil-Arílico), esta ligação em uma estrutura contínua forma grandes moléculas com conformação em espiral, como visto em modelo virtual. Com base nesta idéia, ligninas que possuem alto/baixo teor de β-O-4, podem ter estruturas espiraladas diferenciadas, sugerindo comportamentos diferentes sobre as propriedades da madeira. Isto mostra que as ligninas de angiospermas ((Guaicílica:Siringilica) (GS)), que possuem mais alto teor de β-O-4, por exemplo, apresentariam uma conformação mais espiralar do que as ligninas de gimnospermas (HG). Por outro lado, as ligninas HG possuem mais chances de serem ancoradas sobre a substância matriz do que as ligninas GS. Neste contexto, ligações β-O-4 das ligninas afetam as propriedades da madeira, portanto, isto pode ser considerado relevante para discussão em ciência e tecnologia da madeira.